2018
DOI: 10.1007/s11250-018-1510-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of real-time PCR assay for the detection of Mycoplasma bovis

Abstract: Mycoplasma bovis is one of the important bovine mycoplasma involved in economically important clinical conditions like respiratory diseases, otitis media, and mastitis. The present study was undertaken with the objective of developing a SYBR Green dye-based real-time PCR assay targeting uvrC gene for the diagnosis of M. bovis. The analytical sensitivity and specificity of the assay were evaluated. The test showed 10-fold more sensitivity than conventional PCR and detected down to 100 fg level of DNA. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Furthermore, a selective broth-enrichment step increases the probability of Mycoplasma recovery when compared to direct plating on agar [ 55 ]. In the real-time PCR assay [ 45 ], milk samples from dairies and lung tissue samples were culture-enriched in PPLO broth for 24 h before analysis. In another qPCR for M. bovis testing [ 46 ], the nasopharyngeal swabs were cultured for 3–5 days before the analysis.…”
Section: Currently Used Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a selective broth-enrichment step increases the probability of Mycoplasma recovery when compared to direct plating on agar [ 55 ]. In the real-time PCR assay [ 45 ], milk samples from dairies and lung tissue samples were culture-enriched in PPLO broth for 24 h before analysis. In another qPCR for M. bovis testing [ 46 ], the nasopharyngeal swabs were cultured for 3–5 days before the analysis.…”
Section: Currently Used Diagnostic Methodsmentioning
confidence: 99%
“…It is also possible to detect M. bovis in processed semen [ 2 , 48 ]. The real-time PCR assays are characterised often by a low limit of detection (LOD) and specificity near to 100% [ 45 , 46 , 47 , 48 ]. Taking into consideration that the number of mycoplasmas that are shed during the infection is about >1 × 10 6 CFU/mL in milk [ 4 ] and the LOD for real-time PCR for M. bovis detection in milk is 1.3 × 10 2 CFU/mL [ 48 ], the probability of the detection of infected cow in a herd is high.…”
Section: Currently Used Diagnostic Methodsmentioning
confidence: 99%
“…Conversely, our profile measurements on as1-casein-derived peptides (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and in clinical mastitic goat milk found a good parallel with quantitative data through more accurate methods on bovine milk counterparts [40,45,53], which proved the concomitant over-representation the smaller molecular homologs and down-representation of the larger parental compound species. In this case, some bovine peptide counterparts were proved to have antimicrobial activity against Gram-positive and Gram-negative bacteria, and yeasts [84].…”
Section: Maldi-tof-ms Peptide Profilingmentioning
confidence: 80%
“…On the other hand, MALDI-TOF-MS-based peptide profiling experiments indicated that all fragments from serum amyloid A3, i.e., (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), were down-represented in subclinical and clinical mastitis goat milk samples, notwithstanding their SCC value, thus suggesting reduced proteolysis of this protein after disease outcome. Variably represented fragments originating from proteolysis of serum amyloid A have already been reported in bovine milk from an experimental model of Streptococcus uberis mastitis [45], but none of the previously ascertained molecules matched the ones described here for infected goat milk.…”
Section: Maldi-tof-ms Peptide Profilingmentioning
confidence: 99%
See 1 more Smart Citation